(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Advertising is multi-dimensional. It is a form ofpowerful marketing tool, a component of the economic system, a means offinancing the mass media, a social institution, an instrument of businessmanagement, a field of employment and a profession.